EVALUASI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS)DI SMK TELEKOMUNIKASI TUNAS HARAPAN KABUPATEN SEMARANG (STUDI TENTANG PEMBELAJARAN PAKEM) - Widyatmoko, Prima; Ismanto, Bambang (Universitas Kristen Satya Wacana, 2015)
This study aims at evaluating (a) the design of implementation of PAKEM learningÂ in SMK Telekomunikasi Tunas Harapan, (b) the installation of implementation of PAKEMÂ learning in SMK Telekomunikasi Tunas Harapan, (c) the process of implementation ofÂ PAKEM learning in SMK Telekomunikasi Tunas Harapan, and (d) the productÂ evaluation of implementation of PAKEM learning in SMK Telekomunikasi TunasÂ Harapan. This is a evaluative research employing Discrepency Evaluation Model.Â Techniques of collecting data used are interview, queationaires, documentations study,Â and observation. Triangulation technique is used to support data validity.Â The results of this study are (a) the design of implementation of PAKEM learningÂ has been formulated with regard to educators criteria including input, process, andÂ output aspects, (b) there is still 2% discrepency in teachersâ certificates. QualificationsÂ of teachersâ academic and teachersâ competencies in PAKEM learning are in line withÂ the standards determined, (c) criteria of succesful PAKEM learning program have not been fulfiled entirely. Syllabus and lesson plan preparation reach 85%. Active learningÂ process goes to low discrepency (13%). Creative learning process goes to moderateÂ discrepency (31%). Effective learning process goes to low discrepency (18%). FunÂ learning process goes to low discrepency (15%). In learning achievement assessment,Â teachers have done their responsibilities well, (d) the products in PAKEM learningÂ include achievement in affective aspect where 90% students gain predicate âgoodâ,Â cognitive aspect where 80% students gain B-, and psychomotoric aspect where 79%Â students gain B-.